Evidence of Floral Reversion during In vitro Shoot Regeneration from Young Inflorescence of the Medicinal Geophyte Gloriosa superba L. - Sen, Supriyo; Krishnasamy, V.; Krishnaveni, S.; Vijayalakshmi, C.; Rajamani, K.; Gnanam, R. (Plant Tissue Culture and Biotechnology, 2013)
Plant Tissue Cult. & Biotech. 23(1): 115?120, 2013 (June) DOI: http://dx.doi.org/10.3329/ptcb.v23i1.15568